Kebijakan Pemerintah Jepang Dalam Pengelolaan Limbah Nuklir Di Tahun 2023: Dampak Terhadap Persepsi Publik Internasional - Yesarela Ebenhaezer; Novriest Umbu W. Nau; Roberto Octavianus Cornelis Seba (VISA: Journal of Vision and Ideas, 2024)
Japan is one of the countries that uses nuclear energy as one of its energy sources. As part of its responsibilities, this country also participates in maintaining nuclear safety, public safety, and environmental protection by engaging with the IAEA and UNCLOS. However, following the natural disaster in 2011, several nuclear reactors experienced leaks that contaminated the marine environment, prompting the government and TEPCO to mitigate the situation by storing the processed waste in new tanks. Several years later, these storage tanks reached full capacity, necessitating the disposal of the waste. Consequently, the government implemented a policy to discharge the nuclear waste into the Pacific Ocean. This policy inevitably sparked both support and opposition from the international community, considering cultural, economic, and political perspectives. This study aims to explain the impact on the international public regarding the disposal of nuclear waste into the Pacific Ocean as part of the Japanese government’s policy in 2023. The research method used in this study is qualitative data analysis, where data collection is based on various documents or records of previous occurrences. This nuclear waste disposal has become a focal point for the international community in scrutinizing Japan’s compliance with nuclear safety and environmental laws and how responses are shaped by this policy.